Analisis Pengaruh Tata Kelola Perusahaan, Environmental Sensitivity, Financial Distress, dan Manajemen Laba terhadap Pengungkapan Sukarela Perusahaan Keluarga yang Terdaftar di Bursa Efek Indonesia - Serly Serly (Faculty of Economics, Universitas Internasional Batam, 2021)
The purpose of this research is to analyze the effect of good corporate governance, environmental sensitivity, financial distress, and earnings management on voluntary disclosure in family firms listed on the Indonesian Stock Exchange. Voluntary disclosure is measured by good corporate governance (board activity, board size, non-executive directors, foreign ownership, government ownership, institutional ownership, mangerial ownership, and number of shareholders), environmental sensitivity, financial distress, and earnings management as independent variable. Industry type and firm size as control variable. The data used in this study are the annual reports of non-financial companies listed on the Indonesian Stock Exchange. The target population consists of 139 firms or 695 firm-year observations of companies listed on the Indonesia Stock Exchange for the period 2011-2015. The data obtained were tested with panel regression. The results show that board size, number of shareholders, environmental sensitivity, and firm size have positive significant impact on voluntary disclosure. Institutional ownership and financial distress have negative significant impact on voluntary disclosure. In contrast, this research found that board activity, non-executive directors, foreign ownership, government ownership, managerial ownership, earnings management, and leverage have no significant effect on voluntary disclosure.